Pathological mechanisms and crosstalk among various cell death pathways in cardiac involvement of systemic lupus erythematosus - Wei, Jingjing; Wang, Aolong; Li, Bin; Li, Xingyuan; Yu, Rui; Li, Haitao; Wang, Xinlu; Wang, Yongxia; Zhu, Mingjun (Frontiers in Immunology, 2024)
Systemic lupus erythematosus (SLE) is a prevalent autoimmune disease primarily characterized by the involvement of multiple systems and organs. Cardiovascular disease is the primary cause of mortality in patients with SLE, though the mechanisms underlying the increased cardiovascular risk in SLE patients remain unclear. Recent studies indicate that abnormal activation of programmed cell death (PCD) signaling and the crosstalk among various forms of cell death are critical in the immunopathogenesis of SLE. Furthermore, apoptosis, necroptosis, pyroptosis, NETosis, and ferroptosis are recognized as key cellular processes in the pathogenesis of SLE and are closely linked to cardiac involvement. This review uniquely explores the intricate crosstalk between apoptosis, necroptosis, and other cell death pathways, discussing their roles and interactions in the pathogenesis of cardiac involvement in SLE. Investigating the interplay between PCD signaling and cardiac involvement in SLE in understanding the disease's underlying mechanisms and offers opportunities for new therapeutic interventions. The integration of precision medicine and innovative strategies targeting these complex pathways holds promise for enhancing the treatment prospects of SLE with cardiac involvement.